Clinical trials, social movements and bioactivism: notes for a(nother) genealogy of the Brazilian research ethics system - Castro, Rosana (Saúde e Sociedade, 2022)
A significant part of the literature on the genesis of the Brazilian institutions devoted to the ethical regulation of scientific research involving human beings usually recalls international events, such as those that occurred during and after the II World War, as triggers of a global ethical conscience of which Brazil would have taken part. Based on review of literature, and a genealogical approach, this assay investigates how certain events that occurred in Brazil, such as the actions of social movements in face of clinical trials with Norplant in the 1980s and with antiretrovirals in the 1990s, are fundamental for understanding the different moments of institutionalization of research ethics in Brazil, and its political orientations. Based on the reconstruction of these episodes, it is argued that particular contents of public agendas on biomedical scientific practices were anchored in specific contexts of contestation led by social movements, whose political demands were described in notably ethical terms. The historical configuration of research ethics in Brazil gathers subjects, factors, and political struggles that provide it with a dynamic character. Understanding this context demands considering the actions of social movements aimed at the regulation of clinical trials.